The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1161/01.cir.0000112565.60887.1e
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Correlates and Heritability of Flow-Mediated Dilation in the Community

Abstract: Background-Studies in selected samples have linked impaired endothelial function with cardiovascular disease and its risk factors. The clinical correlates and heritability of endothelial function in the community have not been described. Methods and Results-We examined a measure of endothelial function, brachial artery flow-mediated dilation (FMD), expressed as both percent (FMD%) and actual dilation by ultrasound with the occlusion cuff below the elbow in 2883 Framingham Study participants (52.9% women; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
436
8
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 563 publications
(522 citation statements)
references
References 44 publications
49
436
8
19
Order By: Relevance
“…These include brachial artery flow-mediated dilatation and venous occlusion plethysmography 1,23 . Severity of hypertension correlates with impairment of endothelial function and anti-hypertensive therapies that improve endothelial function in addition to lowering blood pressure may be associated with greater improvements in overall cardiovascular risk 1,24,25 .…”
Section: Measuring Endothelial Functionmentioning
confidence: 99%
“…These include brachial artery flow-mediated dilatation and venous occlusion plethysmography 1,23 . Severity of hypertension correlates with impairment of endothelial function and anti-hypertensive therapies that improve endothelial function in addition to lowering blood pressure may be associated with greater improvements in overall cardiovascular risk 1,24,25 .…”
Section: Measuring Endothelial Functionmentioning
confidence: 99%
“…38,39 Measurement of flow-mediated vasodilation (FMD) in the brachial artery using ultrasound is noninvasive and reflects NO production very well. 40,41 It is accepted that measurement of forearm blood flow responses to vasoactive agents and reactive hyperemia is an index of resistance artery endothelial function and that measurement of FMD is an index of conduit artery endothelial function. Recently, finger plethysmography peripheral arterial tonometry has also been used.…”
Section: Endothelial Functionmentioning
confidence: 99%
“…Aging, smoking, obesity, hypertension, dyslipidemia, and diabetes mellitus are well‐known risk factors of endothelial dysfunction 1, 2, 3, 4, 7, 8, 9, 23, 24, 25. We previously showed that ezFMD was significantly correlated with cardiovascular risk factors and endothelial function assessed by FMD in relatively young participants 15.…”
Section: Discussionmentioning
confidence: 99%
“…It is clinically important to assess endothelial function for early detection of atherosclerosis. Several methods have been developed to evaluate endothelial function in humans 3, 4, 5, 6, 7, 8, 9. Measurement of flow‐mediated vasodilation (FMD) in the brachial artery is a noninvasive and broadly applicable method for assessing endothelial function 4, 5, 6, 7, 8, 9.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation